La mission d’avocat dans la Rome impériale d’après la correspondance de Pline le Jeune - Marie Yschard (Criminocorpus)
The various letters of Pliny the Younger, published in the 2nd century, in which he writes about his activity as a lawyer, show to what extent, in his view, the eloquent defense of other people’s interests is important. By comparing himself with Cicero, Pliny values a classical and republican conception of legal practice, which appears to be in competition with a new kind of legal practice, more lucrative, meant for those who do not belong to the leading class. Because his activity as a lawyer collides with his political and social duties, Pliny tries to stick to a code of ethics that he himself draws up for his own practice. His commitment alongside provincial inhabitants, as well as accused governors, reveals that the lawyer plays a key role in the “fair” conduct of a trial.